Training on the Management of Zakat, Infaq and Shadaqah (ZIS) Productive in Kerinjing Village, Tanjung Raja District, Ogan Ilir Regency - Ichsan Hamidi; Sukanto Sukanto; Dirta Pratama Atiyatna; Dwi Darma Puspita Sari (Sricommerce: Journal of Sriwijaya Community Services, 2021)
Zakat, Infaq and Shadaqah (ZIS) are very important pillars in Islam to improve the welfare of the community, especially in rural areas. The correct management of ZIS funds needs to be understood to the village, so that it is not only depleted in consumptive activities, but can be applied in productive activities to improve the economy. The existence of mosques in the village as ZIS fund managers is very important in its distribution appropriately and usefully, so it is necessary to provide training related to the productive management of ZIS to the administrators and youth of mosques in Kerinjing Village. The goal is so that the people in Kerinjing Village can optimize the potential of ZIS collected. This training method uses discussion and counseling to the participants, so as to create a productive training atmosphere and create improved welfare for the community.